Mitochondrial DNA polymorphisms in Nepalese Achhami cattle - Gorkhali, NA; Dhakal, A; Sapkota, S; Sherpa, C; Pokhrel, BR; Kolachhapati, MR; Bhattarai, N (Bangladesh Journal of Animal Science, 2020)
Achhami cattle is claimed to be the world's smallest cattle which is found in Achham district of Sudur Paschim Province of Nepal. A study was carried out to investigate the polymorphism in the control region of the mitochondrial DNA polymorphism in these Achhami cattle. Thirty-seven blood samples were collected from different pocket areas of in Achham district. Our study revealed that Achhami cattle lie significantly within the indicine haplogroups rather than taurine (34 out of 37 samples) manifesting the later introgression by taurine cattle population. The taurine haplogroup, found within Achhami was different than Lulu cattle, which might be from the independent domestication event. Within indicine haplogroup, I1 type haplogroup (64.7%) was found dominant over I2 type haplogroup (35.3%). Achhami cattle revealed its uniqueness as it segregates from Indian cattle for indicine type as well as Chinese cattle for taurine type. In order to understand its ancestry, the whole genome should be studied together with the consideration of more population of cattle from the Asian region. Bang. J. Anim. Sci. 2020. 49 (1): 22-28